Photodynamic therapy: aspects of pain management - Müller-Christmann, Christine; Enk, Alexander; Gholam, Patrick (Journal der Deutschen Dermatologischen Gesellschaft, 2015)
Topical photodynamic therapy (PDT) is a highly effective and safe treatment method for actinic keratoses with an excellent cosmetic outcome and is commonly used for the therapy of large areas of photodamaged skin with multiple clinically manifest and subclinical lesions. However, the major drawback of photodynamic therapy is the pain experienced during the treatment that can be intense and sometimes even intolerable for patients, requiring interruption or termination of the process. Several strategies for controlling pain during photodynamic therapy have been studied but few effective methods are currently available. Therefore, this review puts the spotlight on predictors on pain intensity and aspects of pain management during photodynamic therapy.
Gesehen am 20.05.2020